2012
DOI: 10.1063/1.4745000
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron velocity-map imaging signature of structural evolution of silver-doped lead Zintl anions

Abstract: A set of silver-doped lead Zintl anions, Ag@Pb n − (n = 5-12), have been studied using photoelectron velocity-map imaging spectroscopy and quantum chemical calculation. The structures of Ag@Pb n − (n = 7-9, 11) built upon a square pyramid base, hitherto not considered, were assigned. Overall agreement between the experimental and calculated photoelectron spectra as well as vertical detachment energies allows for structural evolution to be established. The silver atom prefers to stay outside in the n ≤ 6 cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
(54 reference statements)
2
7
0
Order By: Relevance
“…The central column and the right one indicate those from the calculations at PW91/TZ2P level with the scalar option and the spin−orbit option, respectively. We find the orbital levels shown on the left column are close to theoretical results at BHLYP/def2-TZVP level, 38 and the occupied orbital levels from PW91/TZ2P level with the scalar option are also similar. However, the DFT calculation with the spin−orbit option gave quite different orbital levels on the right column of Figure 4 and the corresponding DOS curve in Figure 2 is qualitatively consistent with the experiment spectrum.…”
Section: Considering the Relativistic Effects In Mpbsupporting
confidence: 78%
See 1 more Smart Citation
“…The central column and the right one indicate those from the calculations at PW91/TZ2P level with the scalar option and the spin−orbit option, respectively. We find the orbital levels shown on the left column are close to theoretical results at BHLYP/def2-TZVP level, 38 and the occupied orbital levels from PW91/TZ2P level with the scalar option are also similar. However, the DFT calculation with the spin−orbit option gave quite different orbital levels on the right column of Figure 4 and the corresponding DOS curve in Figure 2 is qualitatively consistent with the experiment spectrum.…”
Section: Considering the Relativistic Effects In Mpbsupporting
confidence: 78%
“…4 Recently, silver-doped lead cluster anions AgPb n − (n = 5−12) were studied using photoelectron imaging spectroscopy and theoretical calculations. 38 Even the predicted orbital levels of AgPb 5 − were not perfectly consistent with the experimental spectrum, the structure were tentatively determined to a Pb 5 trigonal bipyramid combining with the Ag atom. Though all Cu, Ag, and Au have an oxidation state of +1, these elements are more electronegative than the alkali metal elements.…”
Section: Introductionmentioning
confidence: 88%
“…The similar phenomenon was also found by other researchers. [39][40][41] It is interesting to note that the Pb n Au n (n ¼ 2-12) clusters don't exhibit distinct rule of symmetry due to the equal ratio of Pb atoms and Au atoms for Pb n Au n clusters and the Jahn-Teller effects. Additionally, the cluster with a lower symmetry can decrease its total energy to some extent based on the Jahn-Teller theory.…”
Section: Resultsmentioning
confidence: 99%
“…So far, there have been a few experiments on the doped lead clusters from different aspects, such as mass spectrometry ,,, , photodissociation, molecular beam electric deflection, and photoelectron spectroscopy. ,, In an early mass spectrometry experiment, X. Zhang et al produced binary Pb–Co alloy clusters and observed two abundant peaks at [Co@Pb 10 ] − and [Co@Pb 12 ] − , which were assumed to be an endohedral bicapped square antiprism and a Co-centered icosahedron, respectively. Later, the same group generated and analyzed M-Pb cluster anions (M = Cu, Ag, Au) with many binary compositions.…”
Section: Endohedrally Doped Cages Of Ge Sn and Pbmentioning
confidence: 99%
“…H. Xie et al investigated [AgPb n ] − clusters ( n = 5–12) using photoelectron velocity-map imaging spectroscopy and ab initio calculations at the BHLYP/def2-TZVP level for geometry optimization and the RI-MP2/aug-cc-pVTZ-PP level for more accurate single-point energy calculation. By comparing the experimental photoelectron spectra and VDE with the simulated ones, the most probable structures of [Ag@Pb n ] − clusters have been determined.…”
Section: Endohedrally Doped Cages Of Ge Sn and Pbmentioning
confidence: 99%